Pseudonotomastus southerni gen. nov. sp. nov., a new capitellid from the Celtic Sea - Warren, Lynda M.; Parker, Miles (Mémoires du Muséum National d'Histoire Naturelle, Zoologie, 1994)
A new genus and species of Capitellidae has been found in the Celtic Sea off the south coast of Ireland. The genus differs from other genera in having 11 thoracic segments, the first of which is achaetous, the second has capillary chaetae in the notopodia only and the remaining nine have capillary chaetae only. There are no capillary chaetae in the anterior abdominal segments. The type species, P. southerni, often shows a disrinctive colour pattern.
World Polychaeta Database (WPolyDb)